2003
DOI: 10.1034/j.1600-0846.2003.00017.x
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of skin lesions and skin cancer using simple electrical impedance indices

Abstract: There are clear statistical differences between impedance of common lesions and control skin. With some further developments, the impedance technique can be useful as a diagnostic decision support tool for skin cancer assessment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0
3

Year Published

2007
2007
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(39 citation statements)
references
References 20 publications
1
31
0
3
Order By: Relevance
“…Posljednjih godina ove se metode sve češće primjenjuju u detekciji tumorskih promjena u različitim tkivima. Tako se impedancijskom spektrografijom mogu procjenjivati različite tumorske tvorbe na koži, u dojci i na sluznici ženskih reproduktivnih organa (3,4,10,11). Bioimpedacijska mjerenja već su ustaljena u stomatološ-koj praksi korištenjem različitih apeksnih lokatora za određi-www.ascro.hr…”
Section: Uvodunclassified
See 2 more Smart Citations
“…Posljednjih godina ove se metode sve češće primjenjuju u detekciji tumorskih promjena u različitim tkivima. Tako se impedancijskom spektrografijom mogu procjenjivati različite tumorske tvorbe na koži, u dojci i na sluznici ženskih reproduktivnih organa (3,4,10,11). Bioimpedacijska mjerenja već su ustaljena u stomatološ-koj praksi korištenjem različitih apeksnih lokatora za određi-www.ascro.hr…”
Section: Uvodunclassified
“…Lately, these methods have been increasingly used in the detection of tumors in different tissues. Thus, EI spectroscopy can be used to assess different tumor lesions on the skin, breast and female reproductive organs (3,4,10,11). The application of EI measurements has already been established in dentistry through the use of different apex locators for the root canal length de-…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The proper compensation of temperature effects is thus of paramount importance for glucose monitoring and other medical diagnosis tools based on impedance measurements e.g. [1,2,12,23,39]. However, its relevance is not limited to medical applications, but in general concerns non-destructive evaluations of materials using dielectric spectroscopy [28,37].…”
Section: Introductionmentioning
confidence: 99%
“…They measured the impedance characteristics of the skin and its appearance before and after SLS application and reported that various impedance changes could be used for quantitative evaluation of the skin stimulus. From around 2003, the group attempted to develop a new melanoma diagnostic equipment using the same theory [22]. Figure 3 shows outline of electrode they developed.…”
Section: Impedance Measurementsmentioning
confidence: 99%